Cyberbullies - Baber, Jerry; Fabian, Rhonda; Meridian education Corporation; Fabian-Baber Communication (Lawrenceville, NJ : Meridian Education Corporation, 2006)
Uses dramatizations and question and answer sessions to prevent children and teenagers from being bullied by others when using chat rooms, blogs, and instant messaging. Describes possible responses to such abuse and explains the legal issues involving privacy and libel
Title from end credits
Executive producers, Chris Scherer, Meridian Education ; subject matter experts, Dane Smith, Dave Figenshu ; camera, Dane Smith, Dave Figenshu ; editors, Robert Larkin, Bridgett Yachetti, Mose Aimone
DVD format
Keywords: Cyberbullying